EVALUATION OF AQUEOUS FRUIT EXTRACT OF TAMARINDUS INDICA (L) FOR INHIBITION OF TUMOR NECROSIS FACTOR-a AND CYCLO OXYGENASE ENZYMES IN EXPERIMENTAL ANIMAL - Ali, Mohammad Daud; Gupta, Atul Kumar; Naseer, Arif; Mirza, Mohd Aamir; Afzal, Sabir (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The main objective of this study was to assess tumor necrosis factor-Î± (TNF)-Î± and cyclooxygenase enzymes (COX) inhibition potency of Tamarindus indica Linn. in comparison to standard drug (indomethacin). Methods: Three plants are selected for the studies, namely: Aloe vera (L.), Terminalia chebula Reitz., and T. indica Linn. Estimation of TNF-Î± in serum (at 1:10 dilution in PBS) was performed using the immunoenzymatic (ELISA) technique. COX inhibitor screening assay kits were used for estimation of COX. Result: All three plant extracts showed a potent significant inhibition of the COX enzyme as compared to the positive control and standard drug when the animal was administered with 400 mg/kg. These studies indicate that the T. indica plant extract showed significant COX inhibition even at low dose. All the extracts were effective anti-inflammatory in nature, however, T. indica extracts at a dose of 400 mg/kg were found to be most potent. It was found to be comparable with that of Indomethacin 10 mg/kg body weight. Conclusion: The anti-inflammatory activity expressed by all the three plants A. vera (L.), T. chebula Reitz., and T. indica L. Among all three plants T. indica (L) was found to be more active against both TNF-Î± and COX, and it was comparable to standard drug Indomethacin. Need further studies to elucidate the exact secondary metabolite by which these plants express this activity.